Survey of Islamic ruling on apostasy: in the context of freedom of religion - Shekaib Alam, Mohammad; Awang Hamat, Mohd Afandi (2013)
Apostasy in Arabic word is referred to Riddah or Irtidad; which means “to retreat, to retire, to withdraw from or fall back from . Thus, In Islamic Law it is declared that apostasy is going away from Islam or leaving Religion of Islam to another religion or ism which is not acceptable by Allah. However, if someone changes his religion from Judaism into Christianity, he or she will not be considered as apostate according to the teaching of Islam, due to very simple reason that Islam considers itself perfect religion and whatever beliefs are beside it considered as false or dhalalah . Allah says in the holy Quran “Indeed, the religion in the sight of Allah is only Islam. Therefore, this paper will highlight meaning of apostasy, elements which bring someone into apostasy. Muslim Jurists and Scholars have discussed it in detail. Normally, it is divided in three types; which are apostasy of conviction, apostasy of sayings and apostasy of action. This paper will also highlight the conditions of Apostate and also view of different Muslim Jurists or mazhab on apostasy.